Relationships between Knowledge, Attitude, and Practice Behavior for the Prevention of Coronavirus Disease 2019 (COVID-19) Among Registered Nurses - Prapaporn Sangsuwan; Piyawan Pokpalagon; Suchira Chaviboontham (Nursing Research and Innovation Journal, 2026)
Coronavirus disease 2019 (COVID-19) continues to challenge healthcare systems despite the decline in severe cases and deaths since the global pandemic. Although many countries have transitioned COVID-19 to an infectious disease under routine surveillance, new infections continue because of emerging viral variants, waning immunity, and changes in public health measures. Healthcare facilities therefore remain responsible for maintaining effective infection prevention and control strategies to protect healthcare personnel and patients. In Thailand, hospitals continue to implement infection prevention measures in accordance with recommendations from the Ministry of Public Health and the World Health Organization. Registered nurses play a critical role in infection prevention because they provide continuous, direct patient care and are at increased risk of exposure to infectious diseases. During the COVID-19 pandemic, nurses experienced not only a high risk of infection but also substantial physical and psychological burdens. Infections among healthcare workers also contributed to workforce shortages and increased workloads. These challenges underscore the importance of ensuring that nurses possess adequate knowledge, maintain positive attitudes, and consistently practice appropriate infection prevention behaviors. Understanding the relationships among these factors is essential for developing educational and organizational strategies to strengthen preparedness for current and future emerging infectious diseases. This descriptive correlational study aimed to examine registered nurses’ knowledge,attitudes, and preventive practice behaviors regarding COVID-19 prevention and to investigate the relationships among these variables. Bloom’s Taxonomy served as the conceptual framework,describing learning as an interaction among the cognitive (knowledge), affective (attitudes),and psychomotor (practice) domains. According to this framework, knowledge provides the basis for understanding health information, attitudes influence acceptance and motivation, and practice reflects the application of knowledge and attitudes to real-life situations. Positive attitudes facilitate the translation of knowledge into appropriate practice. Participants were recruited using purposive sampling from a tertiary university hospital in Nonthaburi Province, Thailand. Eligible participants were registered nurses currently working in inpatient units, had experience caring for patients with COVID-19, and were willing to participate in the study. The required sample size was calculated using the G*power program with a significance level of .05, a statistical power of .80, and an effect size of .24. The required sample size was 133, with an additional 10% added to account for potential missing data, yielding a total of 146 participants. Four research instruments were used to collect data: a demographic questionnaire,a knowledge questionnaire on COVID-19 prevention, an attitudes questionnaire, and a preventive practice behaviors questionnaire. Data were collected from June to July 2023 during the circulation of the Omicron variant. Ethical approval was obtained before data collection, and written informed consent was obtained from all participants. Descriptive statistics and Spearman’s rank correlation coefficient were used for data analysis, with statistical significance set at p < .05. Most participants were female (91.8%), with a mean age of 29 years (SD = 6.96).Nearly all held a bachelor’s degree in nursing (99.3%). Participants had a mean of 6 years of nursing experience (SD = 6.85) and 2 years of experience caring for patients with COVID-19 (SD = 0.79). Approximately half (50.7%) had received four doses of a COVID-19 vaccine,whereas 41.0% had never attended formal training related to COVID-19 prevention and infection control. Social media was the primary source of COVID-19-related information. Participants demonstrated high levels of knowledge regarding COVID-19 prevention,with 93.8% achieving high knowledge scores (mean = 11.21, SD = 0.99). Likewise, 91.8%reported positive attitudes toward COVID-19 prevention (mean = 35.16, SD = 3.27), and 95.9% demonstrated high levels of preventive practice behaviors (mean = 82.21, SD = 7.36).These findings indicate that registered nurses continued to maintain appropriate infection prevention practices despite the transition from pandemic response to routine disease surveillance. Attitudes toward COVID-19 prevention were positively associated with preventive practice behaviors (r = .45, p < .01), whereas no significant relationship was found between knowledge and preventive practice behaviors (r = .15, p = .08). These findings suggest that knowledge alone may not be sufficient to ensure consistent preventive practices. Instead, positive attitudes appear to play a more influential role in translating knowledge into practice, consistent with Bloom’s Taxonomy. The findings highlight the importance of strengthening both knowledge and positive attitudes through continuous professional education, supportive leadership, simulation-based training, e-learning programs, and regular evidence-based clinical updates. Such strategies may enhance nurses’ preparedness for future emerging infectious disease outbreaks and improve adherence to infection prevention measures. Future multicenter and longitudinal studies should investigate additional factors influencing preventive practice behaviors to support the development of more effective infection prevention interventions for nurses. Keywords: Coronavirus disease 2019, COVID-19, Knowledge, Attitude, Practice behavior,Registered Nurses Author Contributions:PS: Conceptualization, Method and design, Data collection, Data analysis and interpretation,Drafting the manuscript, Revising and editing the manuscript, Final approval of the submitted versionPP: Conceptualization, Method and design, Data analysis and interpretation, Drafting the manuscript, Responding to the Editor, Revising and editing the manuscript, Final approval of the submitted version, and Corresponding with the editor in chiefSC: Conceptualization, Method and design, Data analysis and interpretation, Final approval of the submitted version